Analysis of Speech Function and Mood System of WhatsApp’s Terms of Service - Mohammad Muhyidin (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2019)
This study is aimed to find out the kinds of speech function realizations in Whatsapp’s terms of service and to find out mood types in each clause in WhatsApp’s terms of service. It is analyzed through identification of clauses Mood structures then being classified into four kinds of speech function; Statement, Question, Command and Offer. There are two kinds of clauses. They are 186 clauses of Terms of Service and 150 clauses of Privacy Notices. The mood types found in the text are 139 declarative clauses and 23 imperative clauses on text of Terms of Service. There are 123 clauses of declarative and 18 imperative clauses on the text of Privacy Notices. There are 262 declarative clauses in text, 41 imperative clauses. It means that declarative clauses are the most dominant in the text. The speech functions found are 262 (86, 46%) statements {divided in 139 in Terms of service and 123 in privacy notices}, command is 41 (13, 53%) {divided in 23 in the Terms of service and 18 privacy notices. It can be concluded that the Terms of service and privacy notices are giving information and ask the reader to do something to the users of WhatApps’s applications. WhatApp’s Terms of Service were dominated by declarative as mood types and all of them used statements as speech functions. Privacy Notices were dominated by declarative as mood types and statements as speech functions. It means that WhatsApp’s Terms of Service mostly give information than demand service and privacy notices mostly give the information and contains of demand of users. Keywords: Speech functions, mood types.